New opportunities for neuroprotective therapy of patients in the acute and early recovery period of ischemic stroke - Marine M. Tanashyan; Anton A. Raskurazhev; Kira Ia. Zaslavskaya; Polina I. Kuznetsova; Irina Yu. Merkulova (Терапевтический архив, 2022)
Aim. To evaluate the efficacy and safety of Brainmax in comparison with ethylmethylhydroxypyridine succinate and trimethylhydrazinium propionate in patients with ischemic stroke in the acute and early recovery period.